Hydroacylation of 2-Butyne from the Alcohol or Aldehyde Oxidation Level via Ruthenium Catalyzed C-C Bond Forming Transfer Hydrogenation - Williams, Vanessa M. (2009)
Under the conditions of ruthenium catalyzed transfer hydrogenation, 2-butyne couples to alcohols 1a–1j to deliver α,β-unsaturated ketones 3a–3j in good to excellent isolated yields with complete E-stereoselectivity. Under identical conditions, aldehydes 2a–2j couple to 2-butyne to provide an identical set of α,β-unsaturated ketones 3a–3j in good to excellent isolated yields with complete E-stereoselectivity. Nonsymmetric alkyne 4a couples to alcohol 1d or aldehyde 2d in good yield to deliver enone 3k as a 5:1 mixture of regioisomers. Thus, intermolecular alkyne hydroacylation is achieved from the alcohol or aldehyde oxidation level. In earlier studies employing the same ruthenium catalyst under slightly different conditions, alkynes were coupled to carbonyl partners from the alcohol or aldehyde oxidation level to furnish allylic alcohols. Therefore, under the conditions of C-C bond forming transfer hydrogenation, all oxidation levels of substrate (alcohol or aldehyde) and product (allylic alcohol or α,β-unsaturated ketone) are accessible.